2011
DOI: 10.1089/neu.2010.1637
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Stimulation Accelerates Axonal and Functional Peripheral Nerve Regeneration across Long Gaps

Abstract: Short-term low-frequency electrical stimulation (ESTIM) of proximal peripheral nerve stumps prior to end-to-end coaptation or tubular bridging of small distances has been reported to increase preferential motor reinnervation and functional motor recovery in animal models and human patients undergoing carpal tunnel release surgery. We investigated the effects of ESTIM on regeneration across rat sciatic nerve gaps, which exceed distances that allow spontaneous regeneration. Three different reconstruction approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
48
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(51 citation statements)
references
References 33 publications
0
48
0
Order By: Relevance
“…This finding indicated that the diabetic rats in our study underwent chronic subthreshold stimulation, because the fixed 10 μA intensity utilized in this study was lower than the threshold. Several studies have reported that monophasic stimulation pulses combined with a subthreshold stimulation intensity (1-10 μA) constituted an optimal ES parameter combination that successfully facilitated neuronal cell growth in transected sciatic nerves, as evidenced by a more mature nerve structure with a smaller cross-sectional area, more myelinated fibers, higher axon density, and a higher ratio of blood vessels to total nerve area compared with that in control groups [21,[30][31][32]. Although the pudendal nerve was not crushed or transected in our study, the same stimulation parameters (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…This finding indicated that the diabetic rats in our study underwent chronic subthreshold stimulation, because the fixed 10 μA intensity utilized in this study was lower than the threshold. Several studies have reported that monophasic stimulation pulses combined with a subthreshold stimulation intensity (1-10 μA) constituted an optimal ES parameter combination that successfully facilitated neuronal cell growth in transected sciatic nerves, as evidenced by a more mature nerve structure with a smaller cross-sectional area, more myelinated fibers, higher axon density, and a higher ratio of blood vessels to total nerve area compared with that in control groups [21,[30][31][32]. Although the pudendal nerve was not crushed or transected in our study, the same stimulation parameters (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…96 Previous studies reported that the immediate application of ES following injury led to better nerve regeneration. 97 The intensity of applied ES, frequency, duration, and timing following nerve injury plays an important role in determining tissue healing. It was discovered that introducing a seven-day incubation (delayed ES) period following cell seeding led to an increased rate of regeneration and resulted in enhanced maturity of the neural components within the growth conduit.…”
Section: Effect Of Electrical Stimulation On Neuronsmentioning
confidence: 99%
“…However, the parameters of electrical stimulation appear to be critical for obtaining the desired results. Numerous studies have shown that low-frequency electrical stimulation applied by means of electrodes in direct contact with the nerve after injury and surgical repair may improve nerve regeneration and accelerate reinnervation of the target organs [4], increase nerve fiber density and diameter [5], enhance myelination and angiogenesis [6], and increase nerve growth factor (NGF) [7] and brain-derived neurotrophic factor (BDNF) release and expression [8]. …”
Section: Introductionmentioning
confidence: 99%